Extensive periportal fibrosis due to hepatic iron overload masquerading as mass lesions in a beta-thalassemia major patient: Sonological appearances - Reddy Ravikanth; Denver Steven Pinto; Pooja Majumdar (Apollo Medicine)
Beta-thalassemia major as a condition is dependent on multiple blood transfusions. In patients with multiple blood transfusions, the liver is the initial site of iron deposition progressing from fibrosis to cirrhosis. Ultrasonography diagnosis of liver fibrosis has prognostic significance and is helpful in risk stratification for assessing treatment options. This case report describes the sonological appearances of the liver in a 28-year-old female who was a recipient of regular blood transfusions and subsequently developed hepatic iron overload which presented as extensive periportal fibrosis masquerading as intraparenchymal mass lesions.